Hantavirus Induced Kidney Disease - Mir, Sheema (Frontiers in Medicine, 2022)
Hantavirus induced hemorrhagic fever with renal syndrome (HFRS) is an emerging viral zoonosis affecting up to 200,000 humans annually worldwide. This review article is focused on the recent advances in the mechanism, epidemiology, diagnosis and treatment of hantavirus induced HFRS. The importance of crosstalk between viral and host factors in the design of therapeutic strategies is discussed. Hantavirus induced HFRS is characterized by thrombocytopenia and proteinuria of varying severities. The mechanism of kidney injury appears immunopathological with characteristic deterioration of endothelial cell function and compromised barrier functions of the vasculature. Although the multidisciplinary research efforts have provided insights about the loss of cellular contacts in the endothelium leading to increased permeability, the details of molecular mechanism still remain poorly understood. The epidemiology of hantavirus induced renal failure is associated with viral species and the geographical location of the natural host of the virus. The development of vaccine and antiviral therapeutics is necessary to avoid the potentially sever outbreaks of this zoonotic illness in future. The recent groundbreaking approach to SARS-CoV-2 mRNA vaccine has revolutionized the general field of vaccinology and has provided new direction for the use of this promising platform for widespread vaccine development, including the development hantavirus mRNA vaccine. The combinational therapies specifically targeted to inhibit hantavirus replication and vascular permeability in infected patients will likely improve the disease outcome.